1001 inventions Muslim heritage in our world - Al-Hassani, Salim T. S.; Woodcock, Elizabeth; Saoud, Rabah (Foundation for Science Technology and Civilisation, 2007)
What do coffee beans, torpedoes, surgical scalpels, arches, and observatories all have in common? Were Leonardo da Vinci's flight ideas originals? Who devised the casing for pill capsules, and where did Fibonacci learn to flex his mathematical fingers?The answers to these questions and more can be found in this book.